Solving ump examination timetabling problem using dynamic exploration step counting hill climbing algorithm - Chang, Ling Shing (2022)
Examination timetabling is a process that involves assigning exams to available timeslot and room(s) to satisfy the hard and soft constraints. An example of such constraint includes no clashing, back-to-back examinations, room capacity constraints and many others. These constraints complicate the assignment of examination to available timeslot and room(s). UMP currently operates from two separate campuses in Gambang and Pekan, Pahang, Malaysia. Operating from two distant campuses forms new constraints different from those reported in the literature. These new constraints further complicate the problem in obtaining a feasible and quality examination timetable. Furthermore, there is no formal mathematical model to assist UMP in evaluating the quality of the examination timetable. Therefore, this forms the motivation of this research to solve the UMP examination timetabling problem with the new examination constraints. The work starts by developing a formal mathematical model based on the new constraints and generates a feasible initial solution of the examination timetable that satisfies the hard and soft constraints (as much as possible). Then, the initial solution is improved using our enhanced algorithm called dynamic exploration step counting hill climbing (DESCHC). The DESCHC employs a dynamic decay rate value to encourage exploration of the search space. The cost bound that acts as the level of acceptance dynamically changes depending on the acceptance of the candidate and improvement in the penalty cost. Experimental results show that DESCHC was able to produce quality solutions. In semester 1-2014/2015, DESCHC produced a solution that is 92.86% better than the UMP examination timetable. In semester 2-2014/2015, DESCHC produced a solution that is 96.13% better than the UMP examination timetable. Moreover, the solution produced by DESCHC satisfies all of the hard constraints that the UMP examination timetable failed to achieve.